Case Report of Concomitant Presentation of Ovarian Torsion and Acute Appendicitis in a Patient Post-Hysterectomy - Eric Schmitt; Krystal Glasford; Samantha Carson; Christopher Rosemeyer (Reproductive Medicine)
Background: Diagnoses for right lower quadrant pain in women must include both gynecologic and non-gynecologic causes. In this differential, ovarian torsion and appendicitis are both serious etiologies that can require swift surgical intervention. Ovarian torsion is the least common of the two, accounting for 2.7% of emergency surgery cases according to a 10-year review, while the lifetime risk of appendectomy for females is 23.1%. As many as 2–3% of patients undergoing surgery for acute appendicitis are instead found to have ovarian torsion. However, there are currently only rare case reports of these two conditions co-presenting in the same patient simultaneously, with little discussion on how to be better prepared before entering the operating room. Objective: The purpose of this study is to describe this rare co-presentation to better inform providers of this potential complication and to improve future patient care outcomes. Method: A case report of a patient seen at Tripler Army Medical Center, Honolulu, Hawaii, was assessed. Conclusions: This case shows the rare possibility of dual acute etiologies of abdominal pain warranting urgent surgical management. This case also highlights the need for a multidisciplinary approach in the pre-procedural evaluation of possible competing etiologies of acute abdominal pain that warrant surgical management. Additionally, this case brings up interesting ethical questions regarding informed consent, autonomy, and the obligation of intraoperatively consulted surgeons to provide definitive and indicated surgical care in the absence of prior discussion of possible pathology.